Cholesterol improves the transfection efficiency of polyallylamine as a non-viral gene delivery vector - Reza Kazemi Oskuee; Mahdieh Ramezanpour; Leila Gholami; Bizhan Malaekeh-Nikouei (Universidade de São Paulo, 2017)
ABSTRACT Cationic polymers such as polyallylamine (PAA) having primary amino groups are poor transfection agents and possess a high cytotoxicity index when used without any chemical modification. In this study, PAA was modified with cholesterol in order to improve transfection efficiency and to reduce cytotoxicity. PAA polymers with molecular weights of 15 and 65 kDa were selected and grafted with cholesterol at percentages of 5, 10, 15, 30, and 50. After purification, the efficacy of the synthetic vectors was evaluated in terms of DNA condensation using the ethidium bromide test, buffering capacity, particle size, zeta potential, transfection efficiency, and cytotoxicity assay in Neuro2A cell lines. According to the ethidium bromide test, these vectors can condense DNA at moderate and high carrier to plasmid (C/P) ratios. The buffering capacity of the prepared vector in both molecular weights was less than unmodified PAA. Particle size measurements demonstrated that modified PAAs were able to form nanoparticles ranging in size from 125 to 530 nm. The vectors based on PAA 15 kDa demonstrated a better transfection efficiency than the vectors made of PAA 65 kDa. Cytotoxicity studies showed that toxicity of all vectors was less than PAA. Some cholesterol modified polymers composed of PAA (15 kDa) were suitable vectors for gene delivery with low cytotoxicity.